Physical determinants of interval sprint times in youth soccer players - Amonette, W. E.; Brown, D.; Dupler, T. L.; Xu, J.; Tufano, J. J.; De Witt, J. K. (Journal of Human Kinetics, 2014)
Relationships between sprinting speed, body mass, and vertical jump kinetics were assessed in 243 male soccer athletes ranging from 10-19 years. Participants ran a maximal 36.6 meter sprint; times at 9.1 (10 y) and 36.6 m (40 y) were determined using an electronic timing system. Body mass was measured by means of an electronic scale and body composition using a 3-site skinfold measurement completed by a skilled technician. Countermovement vertical jumps were performed on a force platform - from this test peak force was measured and peak power and vertical jump height were calculated. It was determined that age (r=-0.59; p<0.01), body mass (r=-0.52; p<0.01), lean mass (r=-0.61; p<0.01), vertical jump height (r=-0.67; p<0.01), peak power (r=-0.64; p<0.01), and peak force (r=-0.56; p<0.01) were correlated with time at 9.1 meters. Time-to-complete a 36.6 meter sprint was correlated with age (r=-0.71; p<0.01), body mass (r=- 0.67; p<0.01), lean mass (r=-0.76; p<0.01), vertical jump height (r=-0.75; p<0.01), peak power (r=-0.78; p<0.01), and peak force (r=-0.69; p<0.01). These data indicate that soccer coaches desiring to improve speed in their athletes should devote substantive time to fitness programs that increase lean body mass and vertical force as well as power generating capabilities of their athletes. Additionally, vertical jump testing, with or without a force platform, may be a useful tool to screen soccer athletes for speed potential.